Clinicopathological characteristics and survival outcomes in Paget disease: a SEER population‐based study - Zhao, Yang; Sun, He‐Fen; Chen, Meng‐Ting; Gao, Shui‐Ping; Li, Liang‐Dong; Jiang, Hong‐lin; Jin, Wei (Cancer medicine (Malden, MA), 2018)
The objective of this study was to investigate the clinicopathological characteristics and survival outcomes of Paget disease (PD), Paget disease concomitant infiltrating duct carcinoma (PD‐IDC), and Paget disease concomitant intraductal carcinoma (PD‐DCIS). We identified 501,631 female patients from 2000 to 2013 in the Surveillance, Epidemiology, and End Results (SEER) database. These identified patients included patients with PD (n = 469), patients with PD‐IDC (n = 1832), and patients with PD‐DCIS (n = 1130) and infiltrating ductal carcinoma (IDC) (n = 498,076). Then, we compared the clinical characteristics of these patients with those who were diagnosed with IDC during the same period. The outcomes of these subtypes of breast carcinoma were different. Based on the overall survival, the patients with PD‐IDC had the worst prognosis (5‐year survival rate = 84.1%). The PD‐DCIS had the best prognosis (5‐year survival rate = 97.5%). Besides, among patients with Paget disease, the one who was married had a better prognosis than who were not. And, according to our research, the marital status was associated with the hormone receptor status in patients with PD‐IDC. Among three subtypes of Paget disease, patients with PD‐IDC had the worst prognosis. Besides, patients who were unmarried had worse outcomes. And the marital status of patients with PD‐IDC is associated with hormone status. The observation underscores the importance of individualized treatment. Patients with PD‐IDC have the worst prognosis. And the marital status of PD‐IDC patients is associated with hormone status and HER2 status. The observation underscores the importance of individualized treatment.